New and interesting species of sacculonotic Haplozetidae (Acari, Oribatida, Haplozetidae) from Indonesia - Ermilov, Sergey G.; Sandmann, Dorothee; Scheu, Stefan (Zootaxa, 2019)
Two new species of haplozetid oribatid mites (Oribatida, Haplozetidae) are described on the basis of adult specimens sampled from litter and soil in Sumatra, Indonesia: Haplozetes bayartogtokhi sp. nov. differs from Haplozetes biheterodactylus Ermilov & Tolstikov, 2015 by the presence of minute interlamellar setae, foveolate anterior part of the notogaster, five pairs of genital setae and the localization of adanal lyrifissures in preanal position; Magyaria leonilae sp. nov. differs from Magyaria annobonica Pérez-Íñigo, 1981 and Magyaria ornata Balogh, 1963 by the presence of bidactylous legs, pointed rostrum and reticulate prodorsum. The species Indoribates hauseri (Mahunka, 1997) comb. nov. (Haplozetidae) is recorded in Indonesia for the first time. A supplementary description for this species is given in detail on the basis of adult specimens from Indonesia and its main morphological traits are summarized. The taxonomic status of the genus Bolkiah Mahunka, 1997 is discussed, resulting in the following new taxonomic proposals: Indoribates (=Bolkiah syn. nov.).